Light Emiting Diode Control System based on the Microcontroller and Smartphone Application - Fahmy Rinanda Saputri; Lucia Blanca Rahawarin (Ultima Computing : Jurnal Sistem Komputer, 2022)
Nowadays, fulfilling the needs of human life requires costs. If the daily needs are under control, then the expense spent to meet the daily needs will also be controlled. In everyday electricity usage, the lights may turn on when the user does not need them. This incident resulted in a waste of electricity and costs. This research designs a Light Emitting Diode (LED) light control system using a microcontroller and smartphone application. The features available in the lamp control application consist of Off and On, Timer, Schedule, Electrical Energy Monitoring, and Automation based on Electricity Billing Budgeting. The tools and software used in the design of the lamp control are: Node MCU ESP8266 version 2, SRD-05VDC-SL-C relay module, ACS712 current sensor, Arduino IDE, MIT App Inventor, and ThingSpeak. The time delay from pressing the ON/OFF button on the smartphone until the light turns on is about 1-6 seconds. The error value for calculating the lamp power with the ACS712 current sensor against the lamp power from the specifications on the light box is 1.3%.